黄遵宪南洋政绩与其文学创作研究 = The study of Huang Zunxian’s political contributions and his literary works in Nanyang - 李俊贤 Lee, Chun Hsien (2013)
黄遵宪（1848-1905），字公度，是晚清著名诗人，也是一名经验丰富的外交官。学界对于黄遵宪的研究相当丰硕，大多以宏观的角度分析黄遵宪的诗集《人境庐诗草》以及透过《日本国志》和《日本杂事诗》来研究黄遵宪在日本的外交仕途。 黄遵宪于1891年至1894年担任首任中国驻新加坡总领事，兼管新马两地的华人事务。在担任新加坡总领事任内，黄遵宪奏开海禁，使华侨归国不再受到欺诈迫害，这项创举受到赞誉“乃中国保护归侨之首倡”，为“公度先生在总领事任内最值得纪念之政绩”。 关于黄遵宪在南洋的事迹，虽有学者论述，但并不详尽，仍有深入考察之必要。本论文将研究范围锁定在南洋，结合文学与历史的研究方法，透过南洋出版的报刊，如《叻报》和《星报》为主要材料，参以实地考察，探讨黄遵宪任职新加坡总领事期间的政绩以及文学创作。 本论文主要有三部分，分别探讨黄遵宪出任新加坡总领事的缘由与政绩、黄遵宪对于新加坡华社的文教贡献、黄遵宪的南洋文学创作。研究发现：在黄遵宪任内，新加坡华社与中国的关系日益密切，文风兴盛；黄遵宪离任后，新加坡华社对于黄遵宪深怀感激之心，南洋一带仍留有关于黄遵宪的遗迹。 Huang Zunxian (1848-1905) was a famous poet during the late Qing Dynasty. On top of that, he was also an experienced and outstanding diplomat. There were numerous researches done on the study of Huang Zunxian, especially on his well-known poems collection Ren Jing Lu Shi Cao and his two other books entitled Ri Ben Guo Zhi and Ri Ben Za Shi Shi (which was a discussion of his diplomatic career in Japan). Huang Zunxian was appointed as the first Consul General in Singapore from the period of 1891 to 1894. During his term of appointment, he was in charge of looking after the overseas Chinese in Nanyang (which includes both Singapore and Malaysia). Furthermore, he filed an appeal to the Qing government to allow the overseas Chinese to return to mainland China without being subjected to any form of oppression, therefore marking one of his many memorable contributions to Singapore as a Consul General. There is, however, a lack of detailed and extensive research done on Huang Zunxian during his stay in Nanyang. Thus the author will focus on this area, by specifically collating relevant information through newspapers articles from both Lat Pau and Sing Pau and conducting field research in the hope of gaining deeper insight into Huang Zunxian’s political contributions and his literary works during this period.